Towards reflexive ethnicity: Museums as sites of intercultural encounter. (8th August 2016) - Walton, Jessica; Paradies, Yin; Mansouri, Fethi
Abstract : In a highly globalised world with increasing ethno‐nationalistic tensions and conflicts, the importance of intercultural education has never been greater. The challenge remains, however, as to whether educating for mutual respect and social cohesion can be achieved through traditional modes of schooling or whether additional approaches that are not necessarily school‐centric are required. Drawing on in‐depth qualitative data including video diaries, narrative interviews and focus groups with Australian secondary school students and semi‐structured interviews with teachers, this paper discusses such an endeavour in which a museum exhibition on identity and belonging is employed as an interactive space for meaningful encounter among students and as a form of professional learning that enlivened teaching practice. Using the concept of reflexive ethnicity, this paper examines whether cognitive and affective encounters outside the 'school gate' create opportunities for critical learning about ethnicity that can complement and enhance school curricula and classroom learning. More importantly, the paper explores how the possibility of building on such activities to create and sustain teaching practice can challenge entrenched static notions of ethnicity. The paper concludes that reflexive encounters with 'difference' within an interactive museum space can unsettle prejudice and provide a deeper and more meaningful understanding of ethnic identity that goes beyond rote classroom learning.